2021
DOI: 10.1136/jmedgenet-2021-107825
|View full text |Cite
|
Sign up to set email alerts
|

New locus underlying auriculocondylar syndrome (ARCND): 430 kb duplication involvingTWIST1regulatory elements

Abstract: BackgroundAuriculocondylar syndrome (ARCND) is a rare genetic disease that affects structures derived from the first and second pharyngeal arches, mainly resulting in micrognathia and auricular malformations. To date, pathogenic variants have been identified in three genes involved in the EDN1-DLX5/6 pathway (PLCB4, GNAI3 and EDN1) and some cases remain unsolved. Here we studied a large unsolved four-generation family.MethodsWe performed linkage analysis, resequencing and Capture-C to investigate the causative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Therefore, it has been suggested that trisomy 7p cases with delayed closure of fontanels can be a result of TWIST gene dosage effect. In addition, in a recent work, Romanelli Tavares et al 20 studying auriculocondylar polygenic syndrome (ARCND) identi ed a unique 430 Kb tandem duplication at the HDAC9/TWIST1 locus that may cause deregulation of TWIST1 expression, interfering with its regulatory elements. This CNV induced the development of ARCND features through compromised neural crest migration and osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that trisomy 7p cases with delayed closure of fontanels can be a result of TWIST gene dosage effect. In addition, in a recent work, Romanelli Tavares et al 20 studying auriculocondylar polygenic syndrome (ARCND) identi ed a unique 430 Kb tandem duplication at the HDAC9/TWIST1 locus that may cause deregulation of TWIST1 expression, interfering with its regulatory elements. This CNV induced the development of ARCND features through compromised neural crest migration and osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that trisomy 7p cases with delayed closure of fontanels can be a result of the TWIST gene dosage effect. In addition, in a recent study, Romanelli Tavares et al [ 23 ], studying auriculocondylar polygenic syndrome (ARCND), identified a unique 430 Kb tandem duplication at the HDAC9/TWIST1 locus that may cause deregulation of TWIST1 expression, interfering with its regulatory elements. By impairing osteogenic differentiation and neural crest migration, this copy number variant led to the development of ARCND characteristics.…”
Section: Discussionmentioning
confidence: 99%